2017
DOI: 10.3389/fcell.2017.00043
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Reprogramming in Glioma

Abstract: Many cancers have long been thought to primarily metabolize glucose for energy production—a phenomenon known as the Warburg Effect, after the classic studies of Otto Warburg in the early twentieth century. Yet cancer cells also utilize other substrates, such as amino acids and fatty acids, to produce raw materials for cellular maintenance and energetic currency to accomplish cellular tasks. The contribution of these substrates is increasingly appreciated in the context of glioma, the most common form of malign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
269
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 266 publications
(300 citation statements)
references
References 237 publications
7
269
2
4
Order By: Relevance
“…Third, the ketogenic diet is a high-fat and low-carbohydrate diet that used in treating gliomas for years [40]. Our results explain to some extent why a ketogenic diet could be an optional therapy for gliomas because unlike normal brain cells, the tumor cells have relatively low expression of CDH18 and UQCRC2, which contributes to the lack of a functional OXPHOS system necessary for metabolism of ketones for energy production [37,39]. However, this hypothesis for ketogenic diet in gliomas needs further investigation.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Third, the ketogenic diet is a high-fat and low-carbohydrate diet that used in treating gliomas for years [40]. Our results explain to some extent why a ketogenic diet could be an optional therapy for gliomas because unlike normal brain cells, the tumor cells have relatively low expression of CDH18 and UQCRC2, which contributes to the lack of a functional OXPHOS system necessary for metabolism of ketones for energy production [37,39]. However, this hypothesis for ketogenic diet in gliomas needs further investigation.…”
Section: Discussionmentioning
confidence: 56%
“…Since CDH18 is firstly studied in gliomas, whether its expression and functions are altered between different molecular subgroups of gliomas remains unexplored. Second, it was revealed that the levels of OXPHOS are down-regulated in glioma cells due to several reasons, one of which is the direct loss of function of components of OXPHOS, such as complex II, III and IV [38,39]. Since UQCRC2 is a core component of complex III, we infer that the down-regulation of CDH18 in gliomas inhibits the expression of UQCRC2 protein, which contributes to the loss of function of complex III and decreased activity of OXPHOS in gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as glioma proliferate, they expand beyond existing blood supply, intensifying the hypoxic environment. Numerous studies point to a molecular escape mechanism that exchanges energy production from aerobic mitochondrial OXPHOS to anaerobic cytoplasmic glycolysis in glioma . Though OXPHOS metabolism provides more ATPs than that in glycolytic metabolism, glycolysis could provide proliferative and survival advantages through decreasing the reliance on aerobic respiration in glioma .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we focused on gliomas, the most common form of primary malignant brain tumor, which can be subdivided into grades II‐IV in light of WHO classification. Compared with WHO Grades II‐III, which comprise LGG, GBM WHO IV bears a dismal prognosis with median survival rates of 14.6 months . The 2016 WHO classification of central nervous system (CNS) tumors combines molecular parameters and histology to define diffuse gliomas .…”
Section: Introductionmentioning
confidence: 99%
“…Compared with WHO Grades II-III, which comprise LGG, GBM WHO IV bears a dismal prognosis with median survival rates of 14.6 months. [14][15][16] The 2016 WHO classification of central nervous system (CNS) tumors combines molecular parameters and histology to define diffuse gliomas. 17 Based on traditional histopathology but enriched with IDH and 1p/19q codeletion status, gliomas could be classified into five subtypes (three LGG and two GBM), as follows: (i) LGG with wild-type IDH (LGG-IDHwt); (ii) LGG with IDH mutation and 1p/19q non-codeletion (LGG-IDHmut-noncodel); (iii) LGG with IDH mutation and 1p/19q codeletion (LGG-IDHmut-codel); (iv) GBM with wild-type IDH (GBM-IDHwt); and (v) GBM with IDH mutation (GBM-IDHmut).…”
Section: Introductionmentioning
confidence: 99%